Assessing the Effects of Pesticides on Aquacultured Fish and Ecosystems: A Comprehensive Environmental Health Review - Emily Burch; Mohamed Ali Hussein; Manar Zaki; Lereen T. Kamal; Ghada Zaki; Tamer Shoeib; Mahmoud Dawood; Hani Sewilam; Anwar Abdelnaser (Fishes)
Aquaculture has been rapidly growing during the past decade to accommodate the increasing need for seafood as a vital source of nutrients for human beings. The nutritional benefits of incorporating fish into one’s diet are paramount in promoting overall health, bolstering immunity and warding off diseases. Nonetheless, farm-raised aquatic species are frequently subjected to elevated contamination levels due to pesticides, antibiotics, and heavy metals in the marine environment. Pesticides affect fish differently based on species, class, dosage, and exposure duration. They can induce histological damage or neurobehavioral changes by inhibiting acetylcholinesterase production. This can promote liver dysfunction, metabolism deregulation, oxidative stress, and hematological imbalances, impair immune responses, and adversely affect fish reproduction. Furthermore, pesticides negatively affect the nutritional composition of fish by reducing the total protein levels in muscle, liver, gills, and kidney tissues. They disrupt lipid metabolism, resulting in lipid accumulation in the liver and a decrease in polyunsaturated fatty acids. Additionally, pesticides interfere with metabolism by altering carbohydrate levels in the gills, muscles, and kidneys while decreasing glycogen storage in the liver. Pesticide exposure has been linked to severe health impacts in humans, such as non-communicable diseases, reproductive issues, cognitive dysfunction, and cancer. The current review comprehensively emphasizes the harmful effects of pesticides on fish and human health, urging the establishment of environmental monitoring programs and biomonitoring studies. It accentuates the need for risk assessment models to evaluate pesticide impacts on marine ecosystems and advocates for stricter safety standards and lower pesticide residue limits in aquaculture products.